The Effect of Fermented Banana Skin Flour on The Growth of Super Kampung Chicken Age 3 - 10 Weeks - I Putu Agus Yudi Subrata; I Gusti Agus Maha Putra Sanjaya; Ni Made Yudiastari (Warmadewa University Press, 2022)
The livestock sector plays a significant role in national food security through the provision of animal protein, especially in the poultry sector, becoming one of the business fields that many Indonesians are looking at, one of which is raising super-village chickens. To get fast growth of chickens and high productivity, sufficient feed is needed that contains the nutrients needed, both in quality and quantity. In order to reduce production costs as small as possible without reducing optimum production, it can be done by utilizing alternative feed ingredients that have high nutritional content, are easy to obtain and are inexpensive, namely banana peel waste. The purpose of this study was to determine the effect of fermented banana peel flour on the growth of 10-week-old super-village chickens. The design used in this study was a completely randomized design (CRD) consisting of 5 treatments and 3 replications, while the treatment was R0 = ration without fermented banana peel flour content. R1 = Ration containing 2.5% fermented banana peel flour. R2 = Ration containing 5% fermented banana peel flour. R3 = Ration with fermented banana peel flour content of 7.5%. R4 = Ration containing 10% fermented banana peel flour. Each treatment was repeated 3 times. The addition of fermented banana peel flour had a very significant effect (P<0.01) on the research variables of weight gain, final body weight and ration consumption. Meanwhile, initial body weight and FCR had no significant difference (P>0.05).